Atomic and electronic structure transformations in SnS2 at high pressures: a joint single crystal X-ray diffraction and DFT study. Issue 9 (28th January 2016) - Filsø, M. Ø.; Eikeland, E.; Zhang, J.; Madsen, S. R.; Iversen, B. B.
Abstract : SnS2 is observed to have a layer compressibility similar to that of graphite, and a reversible color change with pressure is explained from band structure calculations. Abstract : The layered semiconductor SnS2 spurs much interest for both intercalation and optoelectronic applications. Despite the wealth of research in the field of metal dichalcogenides, the structure–property relationship of this compound remains unclear. Here we present a thorough study combining single-crystal X-ray diffraction and DFT calculations on SnS2 in the pressure range 0 < p < 20 GPa. The anisotropic compression of the unit cell is clearly linked to the van der Waals interactions between the S–Sn–S sandwich layers, as the compression mainly affects the interlayer distance. This compression behavior is coincidal with the compression of other well-known layered compounds (graphite and boron nitride) but differs significantly from the compression of other MS2 compounds, making it clear that SnS2 presents a unique and interesting case in the field of metal dichalcogenides. The compression leads to a significant increase in S⋯S interlayer interaction which in turn results in a change in the electronic structure, documented through DFT band structure calculations. The calculated narrowing of the band gap is supported by a significant, reversible color change of the single crystal. At 20 GPa, the size of the band gap has decreased from 2.15 to 0.88 eV, and band gap closure is predicted to occur at 33 GPa.